PENINGKATAN SOFT SKILL PELAYANAN PRIMA BAGI PEKERJA MIGRAN INDONESIA (PMI) DI JOHOR BAHRU MALAYSIA - Panigoro, Hasan S.; Sahami, Femy Mahmud; Amali, Lanto Ningrayati; Malik, Harto (LPPM Uncen, 2024)
Indonesian migrant workers play a vital role in the economy of Johor Bahru, Malaysia, but they face a variety of challenges in their daily lives, even though they often have adequate technical skills for their jobs. Language and cultural differences mean that migrant workers must be able to adjust to new work environments and face diverse job demands. Mastery of essential soft-skills, especially excellent service, is crucial to their success and well-being while living and working. Excellent service soft-skills such as empathy, adaptability, and conflict management often become obstacles, which can directly affect users' perceptions of the services they provide. The solution offered to overcome these problems is to conduct training to improve excellent service soft-skills, which aim to provide knowledge and understanding of the importance of excellent service, effective communication skills, conflict management, empathy, and patience skills, work quality and reliability, readiness to face changes, and ethics and integrity. The implementing activities using an approach method through providing materials and feedback. The material was provided through a short course with an interactive method approach and discussion. This community service activity has succeeded in increasing Indonesian migrant workers understanding of excellent service soft-skills. This is based on feedback from participants who stated that they understood and would strive to apply the concept of excellent service in their daily lives. It is hoped that the excellent service soft-skills improvement strategy that has been provided can become an effective and sustainable foundation and can contribute positively to the quality of their work and welfare in the future and create a harmonious and inclusive environment for Indonesian migrant workers in Johor Bahru, Malaysia.